A Case Study of Teaching Methods, Approaches, and Strategies Found in a Critical Review on Applied Linguistics Course - Al-Faruq, Habibatul Azizah (ELLITE, 2016)
This study investigated the critical review on applied linguistics course teaching methods, approaches, and strategies which would be found in post graduate program in ELT in State University of Malang in the second semester. The lecturer is the teacher who is teaching critical review on applied linguistics course in offering E, class A. This study used one-site case study. Data was gathered from observations. The result of the study showed that the teacher relies on Communicative Language Teaching which was found in the classroom activities. Therefore, this paper critically reviews Intarapanichâ€™s article (2013) â€œTeaching Methods, Approaches and Strategies Found in EFL Classrooms: A Case Study in Lao PDRâ€ on the basis of the nature methods, approaches, and strategies in the teaching EFL classrooms, the existing practice in the teaching of EFL, and for the investigation proposed that teacher should adapt learning activities, based upon student abilities and constraint in classroom setting.Keywords: methods, approaches, strategies, applied linguistic course